Local Government Policies and Participation of Religious Leaders Preventing Sexual Harassment After the Earthquake in Palu, Central Sulawesi - Murni Ratna Sari Alauddin; Maulid Maulid; Indar Ismail Jamaluddin (LPPM IAIN Parepare, 2022)
This study aims to know the local government of Central Sulawesi Province on a temporary provision in preventing women survivors of the earthquake. And to know the actions of religious leaders in preventing sexual harassment of women who survived the earthquake in Palu. The discussion in this article departs from a qualitative descriptive study. Local government officials and religious leaders were the subjects of the interviews. The results showed that the local government in Central Sulawesi indirectly triggered the occurrence and sexual violence experienced by women who survived the earthquake in temporary shelters. This refers to aspects of communication, resources, attitude of implementers. Policy implementers in disaster management. Besides that, the religious leaders have given the role of preventing sexual intercourse with women who survived the earthquake. The varied roles given in preventing and fulfilling government obligations that are negligent towards the victims. Although it is realized that the contributions of these religious leaders are mostly focused on their people.